Challenging the coherence of social justice as a shared nursing value - Lipscomb, Martin (Nursing philosophy, 2011)
Normative and prescriptive claims regarding social justice are often inadequately developed in the nursing literature and, in consequence, they must be rejected in their current form. Thus, claims regarding social justice are frequently presented as mere assertion (without clarification or supporting argument) or, alternatively, when assertions are supported that support may be weak (e.g. social justice is repeated juxtaposed against contentious assumptions regarding market disutility). This paper challenges the coherence of social justice as a shared nursing value and it is suggested that claims regarding the concept should be tempered.